Laser focal point sequestration for Raman micro-spectroscopy of thermally sensitive fuel cell catalytic layers. (1st September 2018) - Loupe, Neili; Doan, Jonathan; Cruse, Ryan; DiMarzio, Charles A.; Smotkin, Eugene S.
Abstract: Intense laser powers used in confocal Raman micro-spectroscopy can photoablate thermally sensitive samples. This has precluded study of the "dark" catalytic layers of hydrogen air fuel cells that consist of carbon supported Pt catalysts embedded in a polymer electrolyte. We now describe how photoablation is mitigated, with retention of z sectioning capability, by lifting the focal point above a transversely homogenous sample surface. This results in a circular conical illumination volume below the focal point. The geometric probability of photons generated in this volume, having pathways to the detector pinhole, is at least two orders of magnitude lower than those emerging from a focal point. However, adequate signal to noise can still be attained by sequestering the laser focal point in an isotropic medium that has no interfering Raman bands. This enables Raman photons from the circular conical illumination volume to dominate the spectra. A finite element model elucidates how incorporation of the isotropic medium for focal point sequestration recovers an order of magnitude in sensitivity. The above methodology provided spectroscopic evidence of the transition of a Nafion exchange site from a protonated sulfonic acid group with no local symmetry, to a dissociated sulfonate exchange site with C3 v symmetry at the onset of the oxygen reduction reaction in a fully operating fuel cell.